Penerapan Asset Based Thinking dalam Kepemimpinan Instruksional Sekolah Penggerak pada SDN Tanah Jambo Aye dan SDN 7 Syamtalira Aron di Kabupaten Aceh Utara - Nurlindayani Nurlindayani; Suparta Rasyid; Yulia Santi (Journal on Education, 2024)
The success of a school in implementing Asset-Based Thinking in instructional leadership for driving schools can influence, motivate, and engage teachers in achieving educational goals. This research focuses on how Asset-Based Thinking is implemented and evaluated in instructional leadership at SD Negeri 6 Tanah Jambo Aye and SD Negeri 7 Syamtalira Aron in North Aceh Regency. This study uses a qualitative approach involving interviews with principals of driving elementary schools in North Aceh Regency. The findings indicate that the implementation of Asset-Based Thinking in instructional leadership requires readiness or creativity from teachers and curriculum representatives in planning and executing Asset-Based Thinking. It is also necessary for them to continually develop themselves through collaboration and participation in training or In-House Training (IHT). The implementation of Asset-Based Thinking in instructional leadership still faces internal challenges, including lack of awareness, unsupported school culture, and limited resources. External challenges include curriculum and evaluation demands, pressure from parents and the community, and changes in educational policies.